Result of immediate prepectoral implant-based breast reconstruction - Rancati, Alberto; Rancati, Agustín; Parapar, Eliana; Mazars, Lucas; Alvarado, Facundo; Lamas, Gonzalo; Butto, Carlos; Dorr, Julio; Angrigiani, Claudio; Bou, Marcelo (Revista Argentina de Cirugía, 2026)
Background: Prepectoral implant-based breast reconstruction has recently been added to the armamentarium for breast reconstruction. This technique provides natural-looking breasts, avoids complications, such as animation deformity, and reduces postoperative pain. Objective: The aim of this study was to describe the surgical outcomes in a series of patients undergoing immediate prepectoral breast reconstruction with silicone implants. Material and methods: A descriptive and retrospective study was carried out with review of the medical records and pathology reports of patients who underwent surgery using the described technique for invasive carcinoma, non-invasive carcinoma, and sarcoma of the breast from March 2018 to December 2021. All the patients were evaluated preoperatively with digital mammography and had fat coverage thickness in the operated breast > 2 cm. Results: A total of 52 reconstructions were performed on 40 patients. Mean age was 52 age (range 30-76). The nipple sparing mastectomy was undertaken in all the cases. There were no major complications during the 40-month average follow-up. None of the patients experienced animation deformity, implant displacement, or rotation. After one year of follow-up, three patients who underwent postmastectomy radiotherapy showed grades III and IV capsular contracture. The aesthetic results were excellent and good in 40 breasts (80.0%), fair in 8 breasts (12.0%) and insufficient in 4 breasts (8.0%). Four breasts (7.7%) required surgical revision in the immediate postoperative period. Conclusions: Immediate prepectoral implant-based breast reconstruction is a feasible technique with enduring results and high level of satisfaction.